Do pandemics spawn extremism?: Spanish flu deaths and the Ku Klux Klan. (30th August 2022) - Chamberlain, Adam; Yanus, Alixandra B.
Abstract : Scholars and journalists connect pandemics to a rise in support for radical political movements. In this study, we draw on this insight to investigate the relationship between the 1918–1919 Spanish influenza pandemic and political extremism—here, the rise of the second Ku Klux Klan—in the United States. Specifically, we ask whether U.S. states and cities with higher death rates from the Spanish flu also had stronger Ku Klux Klan organizations in the early 1920s. Our results do not provide evidence of such a connection; in fact, the data suggest greater Klan membership where the pandemic was less severe. This provides initial evidence that pandemic severity, as measured by mortality, is not necessarily a cause of extremism in the United States; power devaluation as a result of social and cultural change, however, does appear to spur such mobilization.